2019
DOI: 10.1513/annalsats.201811-795oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Exposure and Radiographic Pulmonary Vascular Morphology in the Framingham Heart Study

Abstract: Rationale: Cigarette smoke exposure is a risk factor for many lung diseases, and histologic studies suggest that tobacco-related vasoconstriction and vessel loss plays a role in the development of emphysema. However, it remains unclear how tobacco affects the pulmonary vasculature in general populations with a typical range of tobacco exposure, and whether these changes are detectable by radiographic methods. Objectives: To determine whether tobacco exposure in a generally healthy population manifests as lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…The study population consists of participants of the Framingham Heart Study Offspring and Third Generation cohorts who took part in the Multi-Detector CT 2 sub-study and underwent volumetric thoracic CT between 2008 and 2011 as previously described. 23 , 24 A total of 2470 participants had CT vascular data; those without assessment of any air pollutant were excluded, leaving 2428 individuals in the analysis. This study was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consists of participants of the Framingham Heart Study Offspring and Third Generation cohorts who took part in the Multi-Detector CT 2 sub-study and underwent volumetric thoracic CT between 2008 and 2011 as previously described. 23 , 24 A total of 2470 participants had CT vascular data; those without assessment of any air pollutant were excluded, leaving 2428 individuals in the analysis. This study was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“… 22 Using a related technique in the Framingham Heart Study, we reported a similar association of tobacco exposure with higher volumes of the pulmonary vessels on CT (including the total vascular volume and the volume of the small vessels alone). 23 …”
Section: Introductionmentioning
confidence: 99%
“…Could these differences be explained by the choice of study population? As stated here, Synn and colleagues did not use a novel analysis modality, but their study is the first one to apply it and its algorithm to a large representative and relatively healthy cohort (8). This would also explain why they found an association of smoking with higher pulmonary blood volume, which is the opposite of the previous studies.…”
mentioning
confidence: 92%
“…Another explanation for the smokingassociated increase in pulmonary blood volume was explained by the authors of the study on hand as being a result of a larger appearance of the pulmonary vasculature on imaging by an increased recruitment resulting from a stronger inspiratory effort in healthy smokers. Nevertheless and despite these limitations, Synn and colleagues can reliably conclude that smoking is associated with a higher average total pulmonary vascular volume when compared with nonsmokers in the Framingham study cohort by the use of volumetric imaging (8). In the future, more studies using this modality of larger prospective cohorts of smokers are needed to determine the prognostic relevance.…”
mentioning
confidence: 99%
See 1 more Smart Citation